2020
DOI: 10.3390/foods9070899
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Rambutan Peel Extract by Spray Drying

Abstract: Microencapsulation of bioactive compounds (BC) from rambutan peel by spray drying using DE10 maltodextrin as encapsulating agent was performed. The optimal conditions for the ethanolic extraction of BC were 60 °C, with a time of 1 h, 55% aqueous ethanol and three extraction cycles. The best spray drying encapsulating conditions for BC and antioxidant capacity (AC) were: inlet temperature 160 °C, outlet temperature 80 °C, and 10% encapsulating agent concentration in the feeding solution (core:encapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
2
18
0
3
Order By: Relevance
“…The inlet temperature is generally in the range of 150-220 C. The lower the inlet temperature, the lower is the evaporation rate, and this leads to the high moisture content in the microcapsules (Mohammed et al, 2020). According to Boyano-Orozco et al (2020), the bioactive compounds encapsulated from rambutan peel at 160 C had moisture content of 3.95 ± 0.10% with a high encapsulation efficiency of 85%.…”
Section: Factors Affecting the Encapsulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The inlet temperature is generally in the range of 150-220 C. The lower the inlet temperature, the lower is the evaporation rate, and this leads to the high moisture content in the microcapsules (Mohammed et al, 2020). According to Boyano-Orozco et al (2020), the bioactive compounds encapsulated from rambutan peel at 160 C had moisture content of 3.95 ± 0.10% with a high encapsulation efficiency of 85%.…”
Section: Factors Affecting the Encapsulationmentioning
confidence: 99%
“…In recent times, consumers have developed more interest in food products that have an adequate amount of bioactive components. The main reason is because a lot of research has proved that there is a relationship between the intake of bioactive components and the deterrence of various chronic diseases such as cardiovascular diseases (Boyano‐Orozco et al, 2020). Bioactive compounds, also called nutraceuticals, are those compounds, present naturally, that are essential or nonessential parts of the food chain and possess an advantageous influence on human health (Biesalski et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…TPC was significantly reduced after spray-drying, with an RE of 61%-99% for horseradish root juice and 43%-76% for horseradish leaf juice (Table S1, Supplementary Materials). Boyano-Orozco et al [46] reported an RE of 91%-97% for phenolic compounds in microcapsules of rambutan (Nephelium lappaceum L.) peel extract. According to Pang In all encapsulated samples, the content of phenolic compounds and the AOA were lower compared to the spray-dried juice (blank) due to the included proportion of wall material, which did not contain phenolics, except for the sample with soy protein isolate.…”
Section: Effect Of Horseradish Plant Part On Bioactive Compounds In Mmentioning
confidence: 99%
“…TPC was significantly reduced after spray-drying, with an RE of 61%-99% for horseradish root juice and 43%-76% for horseradish leaf juice (Table S1, Supplementary Materials). Boyano-Orozco et al [46] reported an RE of 91%-97% for phenolic compounds in microcapsules of rambutan (Nephelium lappaceum L.) peel extract. According to Pang et al [47], the retention of phenolic compounds in spray-dried Orthosiphon stamineus extract was effective, ranging from 66.91% (eupatorin) to 82.08% (rosmarinic acid); however, during microencapsulation by spray-drying, phenolic compounds were lost due to high temperature and the action of oxygen, resulting in their destruction and polymerization [27].…”
Section: Effect Of Horseradish Plant Part On Bioactive Compounds In Mmentioning
confidence: 99%
“…Proses yang cukup rumit dan biaya yang relatif mahal serta penampakan flavor yang sedikit berbeda dari bahan alami (39).…”
Section: Kekurangan Dari Pendekatan Mikroenkapsulasiunclassified